The clinico pathological features and survival in serous endometrial cancers - Amrita Datta; Vinotha Thomas; Ajit Sebastian; Rachel George; Anitha Thomas; Thomas Samuel Ram; Sherin Daniel; K. Reka; Abraham Peedicayil (Elsevier, 2023)
Background & Introduction: Serous cancers are a biologically aggressive variety of endometrial cancer (EC) with a high rate of recurrence and mortality among all the subtypes. Herein we describe our experience with serous endometrial cancer. Objective: This study was conducted to identify the clinicopathological characteristics, treatment modalities and survival outcomes in women diagnosed with serous endometrial malignancies. Methods: This was a retrospective descriptive analysis of data on patients diagnosed with serous endometrial tumours between January 2010 to September 2019 in our institute collected from electronic medical records. Descriptive statistics such as proportions, means and standard deviations and Cox regression hazards model on risk factors were performed. Survival was plotted by Kaplan-Meier curves. Results: During the study period, 32 (5.7%) patients out of 564 diagnosed cases of endometrial cancer had serous histology. The mean age at diagnosis was 62.5 years (SD 7.6) while mean BMI was 26.4 kg/m2 (SD 4.6). Staging laparotomy was done in 27(84%) of the patients. Advanced stages (III and IV) were detected in 16 patients (50%) at primary surgery.Adjuvant chemo therapy and radiation was received by 21(65.6%) patients therapy. Out of 32 patients, 13 (40%) developed recurrence while another 13 expired. Stage at diagnosis and type of adjuvant therapy were important factors in determining the outcome. Median recurrence free and overall survival was 22(95% CI 1.4-42) and 36 months (95% CI 10.1-61.8) respectively. Conclusion: Serous endometrial cancers are an intrusive subtype of EC. Comprehensive surgical staging with optimal cytoreduction should be aimed at. Adequate upfront molecular categorization of these tumors is mandated. Adjuvant therapy with chemotherapy and radiation is given in postoperative setting. Targeted therapies and immunotherapy could be considered in recurrences.